GROW-ing Neo-Secularisation - Lorié, Áine (Cultural and religious studies, 2015)
Neo-secularisation theory helps understand the changing position, influence and role of religious authority structures and personal religion/spirituality. This paper discusses the mutual-aid group GROW as an alternative authority system in the context of mental health support in Ireland. Research findings suggest that spiritual and ritualistic dimensions of GROW reinforces a pre-existing religious ethos.